The Interactive Web-Based Learning in Online Learning for Blind Students and Deaf Students in Higher Education - Astuti, Eka Yuli; Ratnawulan, Teti; Santoso, Yoga Budhi; Pertiwi, Dwi Endah; Ridwan, Prinanda Gustarina; Effendi, Zulfa Rahmah (Department of Special Education, 2023)
Online learning has been running in Indonesian universities due to the COVID-19 outbreak. Online learning has become a challenge to both parties, lecturers, and students with special needs. The use of several online platforms for learning has not provided accessibility for students who are blind and deaf. To pursue friendly learning in inclusive classrooms for blind and deaf students, then we need a facility that supports learning for blind and deaf students. The purpose of the study is to develop a learning model that can be used for online learning using an interactive website. The interactive Web-Based Learning Model is an innovative learning model which is designed for special needs students to access online learning more effectively. The procedure used in this interactive web-based learning model is that every blind and deaf student can access learning through various devices connected to their cell phone or laptop to make the learning process two-way and effective. The research was conducted using the research & development method which consists of the stages of producing a model product and then validating and testing the model. The result of this study is an online learning model using a website that can present learning material from lecturers in the form of pages that all the menus can be read directly by blind students through a screen reader on their devices (user friendly) and they can send assignments via voice note options. The website is equipped with videos accompanied by subtitles so that it has accessibility to deaf students. This model consists of the following stages: 1) Planning which includes needs analysis and content analysis, 2) The learning process through an interactive website containing structured learning material, interactive learning through video and discussion features, 3) Evaluation includes test and non-test in the form of process and result in analysis.